Trireme Olympias : the final report : sea trials 1992-4, conference papers 1998 - Rankov, N. B., 1954-; Bockius, Ronald (Oxbow Books, 2012)
"This is the final publication of the Olympias project, which saw the building of a 170-oared Athenian trireme of the fourth century BC and its operation in five series of sea-trials. The first three sea-trials have already been published in separate volumes. The rest of the volume is devoted to papers presenting more recent research on the trireme"--Provided by publisher.